Covid-19 Does Not Stop at Open Borders: Spatial Contagion Among Local Authority Districts During England S First Wave - Laroze-Prehn, D (Elsevier Ltd, 2021)
Infectious diseases generate spatial dependence or contagion not only between individuals but also between geographical units. New infections in one local district do not just depend on properties of the district, but also on the strength of social ties of its population with populations in other districts and their own degree of infectiousness. We show that SARS-CoV-2 infections during the first wave of the pandemic spread across district borders in England as a function of pre-crisis commute to work streams between districts. Crucially, the strength of this spatial contagion depends on the phase of the epidemic. In the first pre-lockdown phase, the spread of the virus across district borders is high. During the lockdown period, the cross-border spread of new infections slows down significantly. Spatial contagion increases again after the lockdown is eased but not statistically significantly so. © 2020
Keywords: SARS-CoV-2; COVID-19; Infectious diseases; Pandemic; Spatial contagion; Spatial dependence; Lockdown; English local authority districts